2021
DOI: 10.1186/s13756-021-01024-4
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of community-acquired bacterial co-infection in patients hospitalized for COVID-19 based on clinical, radiological and microbiological criteria: a retrospective cohort study

Abstract: Background We defined the frequency of respiratory community-acquired bacterial co-infection in patients with COVID-19, i.e. patients with a positive SARS-CoV-2 PCR or a COVID-19 Reporting and Data System (CO-RADS) score ≥ 4, based on a complete clinical assessment, including prior antibiotic use, clinical characteristics, inflammatory markers, chest computed tomography (CT) results and microbiological test results. Methods Our retrospective study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 34 publications
2
20
0
9
Order By: Relevance
“…Looking specifically at respiratory bacterial co-infections, our study found 1.2% of COVID-19 patients with positive cultures in the first three days of hospitalization, in contrast to 6.3% of COVID-19 patients with abnormal cultures representing HAP or VAP by this definition. The low rate of community-acquired respiratory infections we found here further supports these authors’ conclusions that empiric antibiotic therapy for COVID-19 patients is generally not indicated during early hospitalization [10, 11]. Similarly, our finding that non-intubated patients had lower rates of bacterial pneumonia, when those rates were normalized by respiratory culture ordering, argues against routine respiratory culture and empiric pneumonia therapy in these patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Looking specifically at respiratory bacterial co-infections, our study found 1.2% of COVID-19 patients with positive cultures in the first three days of hospitalization, in contrast to 6.3% of COVID-19 patients with abnormal cultures representing HAP or VAP by this definition. The low rate of community-acquired respiratory infections we found here further supports these authors’ conclusions that empiric antibiotic therapy for COVID-19 patients is generally not indicated during early hospitalization [10, 11]. Similarly, our finding that non-intubated patients had lower rates of bacterial pneumonia, when those rates were normalized by respiratory culture ordering, argues against routine respiratory culture and empiric pneumonia therapy in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…We also found similarly low rates of CAP in COVID-19 patients compared to what has previously been cited in the literature. A recent study of hospitalized COVID-19 patients looking specifically at rates of bacterial co-infection within the first three days of hospitalization and finding 1.1% with probable infection, and additional 12.4% with possible co-infection, when all types of infection were considered [10]. Looking specifically at respiratory bacterial co-infections, our study found 1.2% of COVID-19 patients with positive cultures in the first three days of hospitalization, in contrast to 6.3% of COVID-19 patients with abnormal cultures representing HAP or VAP by this definition.…”
Section: Discussionmentioning
confidence: 99%
“…After applying the inclusion and exclusion criteria ( Figure 1 ), a total of 38 articles were included in the qualitative synthesis [ 23 , 24 , 26 , 28 , 29 , 35 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. More precisely, 27 observational studies (see Table 1 for details), 1 case series, and 10 case reports (see Appendix A for details) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 18 cases of co-infections were retrieved (0.4% of total samples), with the majority of studies (18 out of 27, 66.7%) not reporting a single occurrence [ 23 , 24 , 26 , 42 , 44 , 46 , 48 , 50 , 53 , 54 , 55 , 56 , 58 , 59 , 61 , 63 ]. The majority of diagnoses was obtained from studies performed during the “first wave” (61.1%) and in European countries (50.0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation